PENGARUH PENDIDIKAN KESEHATAN MELALUI MEDIA LEAFLET TENTANG INFEKSI MENULAR SEKSUAL TERHADAP TINGKAT PENGETAHUAN SISWA - Bayin Igayanti, Isna; Bachrun, Edy; Prayitno, Suhadi; Wahyu Suryawan, Nashrul (Jurnal Biogenerasi, 2025)
The purpose of this study was to determine the effect of leaflet media on sexually transmitted infections on the knowledge of class X students. The research method uses quantitative with this type of experimental research. The research population was 255 people. The sample size was 72 people. The sampling technique uses simple random sampling. The reasearch design uses a one group pre test post test design. Data collection uses a questionnaire. Statistical tests use the Wilcoxon Signed rank test. The results showed that the average value of knowledge about sexually transmitted infections before the intervention was 15,81 and the average value after the intervention was 26,72. The statistical test resulth with Wilcoxon obtained a p-value 0,000. From the results, it wasobtained a p-value < 0,1 means that Hₒis rejected and Hₗ is accepted, meaning that there is an influence of health aducation through the media leaflet about Sexually Transmitted Infections on the level of knowledge of class X students. The results of the study showed that there were differences in knowledge before and after conducting health education through leaflet media. After conducting health education through leaflet media, respondents had better knowledge. Because health educations is often carried out, information about sexually transmitted infections begins in class X students.